2016
DOI: 10.1039/c6nr03827a
|View full text |Cite
|
Sign up to set email alerts
|

A universal design for a DNA probe providing ratiometric fluorescence detection by generation of silver nanoclusters

Abstract: and singe-nucleotide specificity, expanding the breadth of applicability of these cost-effective probes for biomolecular detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 52 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…The in situ synthesis can obtain the products directly without elaborate molecular design and complicated synthesis. Thus, it is a facile, effective, and controllable way to prepare ratiometric fluorescent probes . In the typical procedure, the precursors and ligands are added to the system simultaneously or sequentially, with the reaction progresses, the ratio fluorescent probe is finally synthesized in situ.…”
Section: Sensor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ synthesis can obtain the products directly without elaborate molecular design and complicated synthesis. Thus, it is a facile, effective, and controllable way to prepare ratiometric fluorescent probes . In the typical procedure, the precursors and ligands are added to the system simultaneously or sequentially, with the reaction progresses, the ratio fluorescent probe is finally synthesized in situ.…”
Section: Sensor Designmentioning
confidence: 99%
“…Their process is the CDs–AuNCs synthesized via situ microwaving a mixture of gold seeds solution (HClAu 4 ) and carbon precursor (glucose). Fygenson's group prepared dual‐emitting DNA‐stabilized Ag NCs using similar in situ technique, which can be used for ratiometric fluorescence DNA detection . Furthermore, Yu's group synthesized the polyethylenimine‐modified Ru(bpy) 3 2+ ‐doped silica nanoparticles according to the Stöber method, which was used as the template particle to grow Ag NCs in situ to prepare dual‐emission PL nanoprobe .…”
Section: Sensor Designmentioning
confidence: 99%
“…[2][3][4] Researchers have collectively reported on Ag N -DNAs stabilized by thousands of different DNA strands, representing a diverse palette of fluorescence properties: emission spectra peaked at 450 nm to 1000 nm, 5,6 quantum yields from 3% to 93%, [7][8][9][10][11][12][13] Stokes shifts up to 0.73 eV (5900 cm −1 ), 14 and light-up or color-switching behavior induced by stimuli. [15][16][17][18] These diverse and sequence-tunable fluorescent Ag N -DNAs are promising for applications ranging from sensing [19][20][21][22] and molecular logic schemes 23 to background-free fluorescence microscopy [24][25][26] and nanophotonics. 10,27,28 Recent breakthroughs are rapidly advancing our understanding of the structures of certain Ag N -DNAs, 5,7,14,[29][30][31] , largely due to detailed studies of about 20 different Ag N -DNA species purified by high performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…Petty and co‐workers reported that by hybridizing with complementary strands, the emission of AgNC could convert from violet to blue–green or near‐infrared . Donnell et al constructed a ratiometric AgNC probe showing distinct fluorescence emission before and after binding with target DNA . A chameleon AgNC obtaining orange‐to‐green fluorescence transformation was designed for Hg 2+ detection .…”
Section: Introductionmentioning
confidence: 99%